The Role Of Ict Adoption And Open Innovation In Affecting Business Resilience In F&B Msmes - Arif Rahmansyah; Keumala Hayati (CV. ITTC INDONESIA, 2026)
MSMEs in the food and beverage (F&B) sector play a strategic role in labor absorption and regional development in Bandar Lampung. However, many business owners still face challenges such as limited innovation and low adoption of digital technology, which hinder their growth and performance in a dynamic market. This study aims to examine the influence of Information and Communication Technology (ICT) adoption and open innovation on the business resilience of F&B MSMEs. Using a quantitative approach, the population of this study consisted of 1,183 F&B MSME owners in Bandar Lampung who utilize ICT. A sample of 112 respondents was determined using the Slovin method with a purposive sampling technique. Data were collected through structured questionnaires with Likert scales and analyzed using multiple linear regression techniques via SPSS 25 software. The results indicate that ICT adoption (β =0,685; p =0,000) and open innovation (β =0,251; p =0,000) have a positive and significant effect on business resilience both partially and simultaneously. The model achieved a coefficient of determination (R2) of 0.694, meaning the independent variables explain 69.4% of the variance in business resilience.The implications of this research emphasize that strengthening internal digital literacy and external knowledge collaboration, particularly customer involvement, is crucial for increasing competitiveness and ensuring the business sustainability of MSMEs amidst local economic pressures.